BIOLOGI REPRODUKSI TUMBUHAN JATI (Tectona grandis) - Karisma Cahyani; Fitriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to understand the reproductive mechanisms of teak (Tectona grandis) both generatively and vegetatively, and their relationship to global conservation status. The methods used were field observations and literature studies from various reliable scientific sources. The results of the study indicate that generative reproduction of teak occurs through the process of flowering, pollination by insects, and the formation of seeds that have natural dormancy. Meanwhile, vegetative reproduction is carried out through techniques such as cuttings and tissue culture, which are more efficient in cultivation because they produce uniform plants. Furthermore, based on global conservation data, teak is included in the endangered category. Thus, both reproductive methods play an important role in supporting the preservation and development of teak plants.